The Feasibility of Using Coxiella burnetii Avirulent Nine Mile Phase II Viable Bacteria as a Live Attenuated Vaccine Against Q fever - Kumaresan, Venkatesh; Alam, Shawkat; Zhang, Yan; Zhang, Guoquan (Frontiers in Immunology, 2021)
This study aimed to explore if viable C. burnetii avirulent Nine Mile phase II (NMII) can elicit protective immunity against virulent NM phase I (NMI) infection. Interestingly, mice immunized with viable NMII elicited significant protection against NMI infection at different time points post-immunization. Viable NMII induced a dose-dependent NMI-specific IgG response in mice but all doses of NMII-immunized mice conferred a similar level of protection. Comparing different route of immunization indicated that intranasal immunized mice showed significant higher levels of protection than other immunization route. The observation that viable NMII induced a similar level of long-term protection against NMI challenge as the formalin-inactivated NMI vaccine (PIV) suggests that viable NMII bacteria can induce a similar level of long-term protection against virulent NMI challenge as the PIV. Viable NMII also induced significant protection against challenge with virulent Priscilla and Scurry strains, suggesting that viable NMII can elicit broad protection. Immune sera and splenocytes from viable NMII-immunized mice are protective against NMI infection but immune sera receiving mice did not control NMI replication. Additionally, viable NMII conferred a comparable level of protection in Wild type, CD4+ T cell deficient, and CD8+ T cell deficient mice, and partial protection in B cell deficient mice. However, NMII-immunized T cell deficient mice were unable to prevent C. burnetii replication. Thus, both B cells and T cells are required for viable NMII-induced protective immunity but T cells may play a critical role. Collectively, this study demonstrates the feasibility of using avirulent NMII as a live attenuated vaccine against human Q fever.